Nutrition in Ancient Peru - Guzmán Barrón, Alberto (1955)
At the suggestion of my teacher Professor Carlos Monge, I have the honor to participate is this interesting Anthropology Conference. Dedicated exclusively to Biochemistry understood that my historical knowledge is scarce, when they had earned some references from people who have dealt with these issues, particularly those published by Professor Juan B. Lastres, to treat it entirely from the nutritional point of view .